Unveiling the conservation status of the sessile oak forest for their protection and management in the northeast of the Iberian Peninsula - Bou, Jordi; Vilar, Lluís (Mediterranean Botany, 2021)
The sessile oak forests found on the northeast of the Iberian Peninsula are ascribed to the Lathyro-Quercetum petraeae association and play a key role in understanding the ecology of this habitat, as this region represents its xeric limit. For this reason, we analysed the biodiversity patterns and current conservation status of the sessile oak forests in the region. To do so, we collected Braun-Blanquet inventories of 34 plots randomly distributed throughout the sessile oak forests. The results showed a relationship between the climatic conditions and the biodiversity variables. While the richness of the community increased with decreasing temperatures, the characteristic species found within the community decreased at these same temperatures. This result was due to the presence of most companion species in the cool zones at high elevations. Sessile oaks are found close to other communities, such as silver birches and Scot pine forests. On the other hand, in the warm areas at low elevations, the sessile oak community was more established, with plants typical of this type of forest. These slightly warmer zones with sessile oaks are very important in terms of conservation and more vulnerable to climate change and the thermophilization of the community, as has been studied. As such, protecting and managing these forests is key to conserving this community. Nevertheless, as current protection measures do not safeguard most of these forests, it is essential to define a conservation strategy to preserve them. Using the conservation status, we have established criteria to improve the conservation strategy for sessile oak forest on the NE Iberian Peninsula.